Effectiveness of home‐based exercise in older patients with advanced chronic obstructive pulmonary disease: A 3‐year cohort study. Issue 1 (1st August 2017) - Wakabayashi, Ritsuko; Kusunoki, Yuji; Hattori, Kumiko; Motegi, Takashi; Furutate, Ryuko; Itoh, Aki; Jones, Rupert CM; Hyland, Michael E; Kida, Kozui
Abstract : Aim: To determine whether home‐based exercise can improve clinical outcomes in older patients with advanced chronic obstructive pulmonary disease using long‐term oxygen therapy. Methods: Information was provided to improve chronic obstructive pulmonary disease self‐management before the onset of the present prospective 3‐year cohort study. Patients selected either home‐based exercise using a lower‐limb cycle machine (ergo‐bicycle; group E), or usual exercise (group U). To assess self‐management, the Lung Information Needs Questionnaire was evaluated every 6 months. Clinical outcomes included the 6‐min walk test, pulmonary function tests, the body mass index, airflow obstruction, dyspnea and exercise index, St. George's respiratory questionnaire, and the number of exacerbations and hospitalizations. Results: A total of 136 patients (group E = 72; group U = 64), with a mean age of 74.2 years were enrolled. Total Lung Information Needs Questionnaire scores improved over 3 years for group E ( P = 0.003). The distance of the 6‐min walk test was well maintained in group E, but significantly decreased in group U ( P < 0.001). The percentage of forced expiratory volume in 1 s at baseline was lower in group E ( P = 0.016), but was maintained over 3 years, whereas a significant reduction was seen in group U ( P = 0.001). The body mass index, airflow obstruction, dyspnea and exercise index significantly worsened in both groups over 3 years (group E: P = 0.011; group U: P < 0.001), whereas a significant decrease in the number of exacerbations was noted in group E ( P = 0.009). Conclusions: Patients who undertook home‐based exercise using an ergo‐bicycle were able to maintain clinical outcomes including 6‐min walk test distance and percentage of forced expiratory volume in 1 s predicted, and recorded fewer exacerbations over 3 years.Geriatr Gerontol Int 2018; 18: 42–49 .